Predicting trends and building strategies for consumer engagement in retail environments - Granata, Giuseppe, 1965-; Tartaglione, Andrea Moretta, 1971-; Tsiakis, Theodosios, 1978- (Business Science Reference, 2019)
"This book provides theoretical and practical insights to improve the understanding of retail complex environments and consumers' shopping behaviors thus enabling the prediction of trends and the elaboration of strategies for retail practitioners in the time of retailers' crisis"--